2020
DOI: 10.1002/cae.22211
|View full text |Cite
|
Sign up to set email alerts
|

Approach to generate 3D‐printed terrain models using free software and open data sources: Application to military planning

Abstract: The students of the Defense University Center at the Spanish Naval Academy (Marín, northwest of Spain) attend both the military studies and mechanical engineering degrees. These students are the future officers of the Spanish Navy. Among them, the Marine Corp students attend subjects focused on topography, Geographic Information Systems (GIS) and an amphibious landing. In this framework, this paper presents an example of an application of the use of physical models for a better understanding of the terrain, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…United Kingdom (67), Singapore (66), India (50), Australia (44), and South Korea (44) have TLS of 54, 56, 12, 38, and 18, respectively. It is also noticed that countries with the maximum relationship frequencies according to the frequency of links are the United States (21), Italy (19), the United Kingdom (17), and China (16). Thus, analysis specifies that these countries with maximum links are the central hub for the 4D printing collaborative research.…”
Section: Country Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…United Kingdom (67), Singapore (66), India (50), Australia (44), and South Korea (44) have TLS of 54, 56, 12, 38, and 18, respectively. It is also noticed that countries with the maximum relationship frequencies according to the frequency of links are the United States (21), Italy (19), the United Kingdom (17), and China (16). Thus, analysis specifies that these countries with maximum links are the central hub for the 4D printing collaborative research.…”
Section: Country Participationmentioning
confidence: 99%
“…The management of smart disasters through the assistance of ICT concluded that the disaster management‐related research areas have gained importance with time and are adapting to the current ICT technologies [18]. A methodological approach for producing 3D printing models using open data sources and free license software focuses on the application in military planning [19]. The use of 3D‐printed models in conventional teaching accompanying two‐dimensional maps in education aimed to provide the issues experienced in the topographical survey education, which is reduced by using 3D‐printed models [20].…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative index of registration error includes the total number of registration points, mean distance error and RMSE. In this section, the ICP registrations of 3D point clouds of depth maps and those of the corresponding CAD models are carried out by using CloudCompare 29,30 . The registration results of the cone cavity and end jaw of microgripper are shown in Figures 23 and 24, respectively, and the quantitative indexes of registration error are shown in Table 2.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…The created Vltava River valley 3D model will be used for several purposes, with the main aim of presenting the vanished cultural heritage (Brůna et al., 2014; Pacina & Cajthaml, 2014). Terrain models printed in 3D have gained popularity in recent years as they offer a different way of presenting the spatial features of subject areas (Hasiuk & Harding, 2016; Solla, Casqueiro, & Cuvillo, 2020). Several methods for creating mass 3D models and texture applications have been tested to produce large‐scale 3D models of selected areas, such as 3D printing and computer numerical control (CNC) milling (Cureton, 2017).…”
Section: Introductionmentioning
confidence: 99%